A social identity perspective on conformity to cyber aggression among early adolescents on WhatsApp. Issue 4 (15th February 2021) - Bleize, Daniëlle N. M.; Tanis, Martin; Anschütz, Doeschka J.; Buijzen, Moniek
Abstract: Cyber aggressive behaviors such as nonconsensual image sharing, nasty comments, and social exclusion frequently take place on WhatsApp. These behaviors often involve group processes, where adolescents conform to peers' behaviors. WhatsApp is pre‐eminently suited for group‐communication among adolescents, and, thus, may facilitate conformity to such behaviors. However, research on conformity on WhatsApp is scarce. Therefore, the aim of this study was to examine if and how the social identity perspective on group behavior may explain cyber aggression on WhatsApp. Specifically, we examined how social identification relates to conformity to cyber aggression on WhatsApp. In a preregistered survey, 647 early adolescents answered questions about social identification with group members and conformity to behavior of a WhatsApp group. Hierarchical multiple regression and moderated mediation analyses point toward an indirect, positive relation between the centrality component of social identification and conformity to cyber aggression, mediated by perceived social pressure to conform. These findings contribute to the literature by extending the social identity perspective to conformity on WhatsApp. Further exploration of this research line within the field of cyber aggression is warranted, because this can help improve applied interventions to reduce conformity to cyber aggression.